1982
DOI: 10.1111/j.1471-4159.1982.tb08631.x
|View full text |Cite
|
Sign up to set email alerts
|

Degranulation of Rat Cerebellum Induces Selective Variations in Gene Expression

Abstract: Selective variations in the composition of poly(A)-containing mRNA were found to be induced in the rat cerebellum by X-irradiation. mRNA populations prepared from normal and X-irradiated rat cerebella at different stages of their development displayed equal efficiencies when translated in vitro in reticulocyte lysates. Specific differences were revealed, however, when the labeled translation products of both mRNA preparations were subjected to two-dimensional gel electrophoresis followed by fluorography of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Polyadenylated RNA prepared from these frozen tissues induced the incorporation of [35S]methionine into TCA-insoluble protein in reticulocyte lysates. Both the yield of mRNA and its translation efficiency were lower from brain tissues than from the carcinoma, but close to the values observed using fresh rat cerebellum tissues (Soreq et al, 1982b;Eliyahu and Soreq, 1982). We therefore concluded that all the mRNA preparations were both intact and translatable.…”
Section: Resultssupporting
confidence: 82%
“…Polyadenylated RNA prepared from these frozen tissues induced the incorporation of [35S]methionine into TCA-insoluble protein in reticulocyte lysates. Both the yield of mRNA and its translation efficiency were lower from brain tissues than from the carcinoma, but close to the values observed using fresh rat cerebellum tissues (Soreq et al, 1982b;Eliyahu and Soreq, 1982). We therefore concluded that all the mRNA preparations were both intact and translatable.…”
Section: Resultssupporting
confidence: 82%